Molecular Structure of the Pyruvate Dehydrogenase Complex from Escherichia coli K-12 - Vogel, Otto (1972)
The pyruvate dehydrogenase core complex from E. coli K-12, defined as the multienzyme complex that can be obtained with a unique polypeptide chain composition, has a molecular weight of 3.75 × 10(6). All results obtained agree with the following numerology. The core complex consists of 48 polypeptide chains. There are 16 chains (molecular weight = 100,000) of the pyruvate dehydrogenase component, 16 chains (molecular weight = 80,000) of the dihydrolipoamide dehydrogenase component, and 16 chains (molecular weight = 56,000) of the dihydrolipoamide dehydrogenase component. Usually, but not always, pyruvate dehydrogenase complex is produced in vivo containing at least 2-3 mol more of dimers of the pyruvate dehydrogenase component than the stoichiometric ratio with respect to the core complex. This “excess” component is bound differently than are the eight dimers in the core complex.